MODEL PEMBELAJARAN PENDIDIKAN AGAMA ISLAM DI SEKOLAH UMUM - Agustina, Winda; Hamengkubuwono, Hamengkubuwono; Syahindra, Wandi (AT-TA'DIB: JURNAL ILMIAH PRODI PENDIDIKAN AGAMA ISLAM, 2020)
This study aimed to find out a depiction of PAI learning model at SMKN of Lubuk Ubar in Rejang Lebong, Bengkulu. This study used a qualitative approach, and the data sources were PAI teacher, class teacher, and school principal. This study used observation and interview techniques to gather data as regards objectives of this study. After the data were collected, the next step was to analyze the data using the approach of Miles et al comprised of selecting and mapping data, presenting data, and verifying conclusions. This study drew the following conclusion: the learning model applied by PAI teachers was first an active and cooperative learning model. It referred to a learning model that led students to be active and creative, not just listening, but also carrying out activities such as processing, finding, and utilizing information. Second, the contextual learning model, this model helped educators link between the materials taught and real-world situations experienced by students, so that students could find a relationship between the knowledge they had and its application in their lives as family and community members.